2001
DOI: 10.1007/s002620100206
|View full text |Cite
|
Sign up to set email alerts
|

IgG-recognizing shed tumor-associated antigens can promote tumor invasion and metastasis

Abstract: Tumors secreting glycoproteins that act as tumor-associated antigens have been described as highly invasive and metastatic. In this study, the consequences of the humoral immune response (HIR) against these antigens were investigated. Using an in vitro model of tumor cell invasion, results indicated that the invasiveness of tumor cells secreting antigenic secreted/shed tumor glycoproteins (STGP) increases in the presence of specific anti-STGP IgG, polymorphonuclear cells and monocytes. This in vitro model show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…On the other hand, there is mounting evidence that B cells can also promote tumor cell invasiveness and metastasis. In one study, tumor cells producing antigenic Secreted/shed Tumor GlycoProteins (STGPs) were transplanted into immune-competent mice or mice deficient in T cells [248]. In both mouse lines, increased tumor cell invasion correlated with an increase in serum anti-STPG IgG levels and tumoral infiltration of cells of the innate and adaptive immune system.…”
Section: The Adaptive Immune System and Metastasismentioning
confidence: 99%
“…On the other hand, there is mounting evidence that B cells can also promote tumor cell invasiveness and metastasis. In one study, tumor cells producing antigenic Secreted/shed Tumor GlycoProteins (STGPs) were transplanted into immune-competent mice or mice deficient in T cells [248]. In both mouse lines, increased tumor cell invasion correlated with an increase in serum anti-STPG IgG levels and tumoral infiltration of cells of the innate and adaptive immune system.…”
Section: The Adaptive Immune System and Metastasismentioning
confidence: 99%
“…However, the biological effects of antibodies cannot be assessed from their antigen binding properties. Tumor cells secreting antigenic secreted/shed tumor glycoproteins can induce a host IgG immune response that can promote invasion and metastasis by inducing tumor infiltrating stromal cells to release proinflammatory cytokines and VEGF [18]. Although the exact mechanism of antibody enhancement of tumor growth remains unclear, it was hypothesized that antibodies may do so by blocking target epitopes on the cancer cells [19].…”
Section: Discussionmentioning
confidence: 99%
“…These immunosuppressive mechanisms typically occur in a manner that does not require antigen recognition by the BCR ( Shah et al, 2005 ). Yet other studies have suggested that the production of antibodies themselves may promote tumor progression and metastasis by activation of Fc Receptors (FcRs) on myeloid cells, induction of tumor-intrinsic signaling through activation of surface receptors, promotion of pro-inflammatory granulocyte responses, promotion of angiogenesis, and suppression of cellular immunity ( Qin et al, 1998 ; Pucci et al, 2016 ; Gu et al, 2019 ; Andreu et al, 2010 ; Barbera-Guillem et al, 1999 ; Nyhus et al, 2001 ; Tan and Coussens, 2007 ).…”
Section: Systems Approaches To Understanding the Roles Of Specific Immentioning
confidence: 99%